2013
DOI: 10.1089/apc.2012.0439
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Treatment Interruption and Loss to Follow-Up in Two HIV Cohorts in Australia and Asia: Implications for ‘Test and Treat’ Prevention Strategy

Abstract: Both antiretroviral treatment interruption (TI) and cessation have been strongly discouraged since 2006. We describe the incidence, duration, and risk factors for TI and loss-to-follow-up (LTFU) rates across 13 countries. and ART with food restrictions (fasting or with food). In conclusion, since 2006, 7.8% of patients had significant time off treatment, which has the potential to compromise any 'test and treat' policy as during the interruption viral load will rebound and increase the risk of transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
4
13
0
Order By: Relevance
“…A linkage study of the Australian HIV Observational Database (AHOD), which has an LTFU rate similar to that of TAHOD, revealed that being LTFU was not associated with increased risk of mortality. 30,31 Overall, the effects of other adjusted characteristics in the regression models are consistent with previous findings. 4,12,16,32,33 Age and CD4 count were both significantly associated with the three treatment outcomes.…”
Section: Ten Years Of Cart In Tahod 777supporting
confidence: 89%
“…A linkage study of the Australian HIV Observational Database (AHOD), which has an LTFU rate similar to that of TAHOD, revealed that being LTFU was not associated with increased risk of mortality. 30,31 Overall, the effects of other adjusted characteristics in the regression models are consistent with previous findings. 4,12,16,32,33 Age and CD4 count were both significantly associated with the three treatment outcomes.…”
Section: Ten Years Of Cart In Tahod 777supporting
confidence: 89%
“…Patients experiencing AEs are more likely to have treatment modifications, interruptions and/or discontinuations . Although the prevalence of TIs has fallen over recent years, drug toxicities and side effects have remained the most common causes of TI . Unplanned cART interruptions may be unavoidable when there are drug stock‐outs, to manage cART‐related AEs, or when there are adherence challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment has become more widely available, but few data have been published on rates of retention and predictors of loss to follow-up (LTFU) among people at highrisk of HIV-infection enrolled on immediate ART. Studies carried out in the general population have shown that LTFU ranged between 14 and 18% for the people living with HIV initiated on ART with some studies indicating that 41% of the LTFU occurred within the first 6 months of ART initiation [16][17][18]. We build on this work with a cohort of HIV positive women who started ART in a "Test and Treat" facility in Kampala, Uganda during the period of August 2014 to March 2018.…”
mentioning
confidence: 99%